Development and Validation GC/MS Method for Methamphetamine Analysis in Urine by Miniaturization QuEChERS - Soraya Aulia; Riesta Primaharinastiti; Djoko Agus Purwanto (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
This paper explains the development of a quick and easy gas chromatography (GC) approach to identify methamphetamine in urine. This research used gas chromatography with mass spectroscopy and a capillary column TG-5SILMS (5% phenyl methyl siloxane, 30 m x 0.32 x 25 m). The carrier gas flow rate was set at 1.0 mL/minute, the temperature inlet and detector had been set at 300°C, and the oven temperature was programmed to initiate at 50°C and held for 1.5 minutes before being raised to 300°C at a rate 40°C/minute and held for 3 minutes. Sample pre-treatment by modification of the QuEChERS method includes using a relatively large amount of inorganic salt, extraction volume and extraction cycle. The optimal conditions for processing a 400 uL urine sample were 160 mg magnesium sulphate, 40 mg sodium chloride, and 400 uL acetonitrile for organic solvent. According to the validation test, the detection limit for methamphetamine was 0.36 ug/mL; the quantitation limit was 1.09 ug/mL, and the calibration curve followed the regression line. y=1.0489x-3.7914, coefficient (r) was 0.9973. The recovery of the analyte spiked into urine at 5, 7 and 9 ug/mL on average was 100.5±2.33% for intraday dan 93.3±7.21% for interday. The precision was excellent, with an average coefficient of variation of 2.31%. The procedure was applied to four urine samples from drug users and the first abuser (25.51 ug/mL), the second abuser (15.05 ug/mL), the third abuser (17.72 ug/mL) and the last abuser (3.08 ug/mL) were all satisfactorily quantitated.